Disruption of skin microbiota contributes to salamander disease. Issue 1885 (22nd August 2018) - Bletz, Molly C.; Kelly, Moira; Sabino-Pinto, Joana; Bales, Emma; Van Praet, Sarah; Bert, Wim; Boyen, Filip; Vences, Miguel; Steinfartz, Sebastian; Pasmans, Frank; Martel, An
Abstract : Escalating occurrences of emerging infectious diseases underscore the importance of understanding microbiome–pathogen interactions. The amphibian cutaneous microbiome is widely studied for its potential to mitigate disease-mediated amphibian declines. Other microbial interactions in this system, however, have been largely neglected in the context of disease outbreaks. European fire salamanders have suffered dramatic population crashes as a result of the newly emerged Batrachochytrium salamandrivorans ( Bsal ). In this paper, we investigate microbial interactions on multiple fronts within this system. We show that wild, healthy fire salamanders maintain complex skin microbiotas containing Bsal -inhibitory members, but these community are present at a remarkably low abundance. Through experimentation, we show that increasing bacterial densities of Bsal -inhibiting bacteria via daily addition slowed disease progression in fire salamanders. Additionally, we find that experimental- Bsal infection elicited subtle changes in the skin microbiome, with selected opportunistic bacteria increasing in relative abundance resulting in septicemic events that coincide with extensive destruction of the epidermis. These results suggest that fire salamander skin, in natural settings, maintains bacterial communities at numbers too low to confer sufficient protection against Bsal, and, in fact, the native skin microbiota can constitute a source of opportunistic bacterial pathogens that contribute to pathogenesis. By shedding light on the complex interaction between the microbiome and a lethal pathogen, these data put the interplay between skin microbiomes and a wildlife disease into a new perspective.